PERKEMBANGAN INDIVIDU - Nurhayati Nurhayati (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Growth is a continuous process, starting from simple conditions to complex conditions. Growth in humans can be analyzed how babies who are weak, dependent, not skillful in nature can be strong, independent and have the skills to face life tests. Individual development is a pattern of movements or changes that dynamically starts from conception or conception and continues throughout the life cycle of human beings that occur as a result of maturity and experience. There are two conflicting processes that occur simultaneously throughout life, namely growth called evolution and setbacks which are called involution. At the beginning of human life the role is evolution, while involution plays a role at the end of life, namely changes that are backward. This attitude towards changes in development is influenced by individual appearance and behavior, cultural stereotypes, cultural values, changes in roles and personal experience. One of the goals of this change is so that individuals are able to adjust to the environment so that both physically and psychologically are in accordance with social expectations